2017
DOI: 10.1007/s13753-017-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Sense of Place on Farming Households’ Relocation Willingness in Areas Threatened by Geological Disasters: Evidence from China

Abstract: Scholars from environmental psychology, geography, disaster science, and sociology have recently focused attention on evacuation and relocation behaviors and influencing factors in hazard-threatened areas. However, existing studies are mainly focused on developed countries and the influence of individual characteristics, household characteristics, and the perception of risk of urban households on evacuation and relocation behaviors. Few studies examine developing countries and the influence of farmers' sense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 49 publications
4
66
2
Order By: Relevance
“…Households make corresponding behavioral decisions only when they perceive the threat of a disaster (Lazo et al 2015;Xu et al 2017b). Thus, household risk perception also affects their behavioral decisions, such as relocation and disaster preparedness (Xu et al 2017a). Lindell's (2013) review concluded that risk perception has a mixture of significant and insignificant correlations with hazard adjustment adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Households make corresponding behavioral decisions only when they perceive the threat of a disaster (Lazo et al 2015;Xu et al 2017b). Thus, household risk perception also affects their behavioral decisions, such as relocation and disaster preparedness (Xu et al 2017a). Lindell's (2013) review concluded that risk perception has a mixture of significant and insignificant correlations with hazard adjustment adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By the end of 2017, there were 30 million impoverished rural people in China who mainly live in some concentrated contiguous poor areas. Affected by geology and topography, geological disasters are frequent in some rural communities in these areas, seriously threatening people's lives and property (Xu et al 2017a). Unlike other factors leading to poverty, geological disasters are characterized by their infrequent occurrence, their abrupt occurrence, and their high degree of severity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations